1999
DOI: 10.1111/j.1751-8369.1999.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithological description of subcropping Lower and Middle Triasic rocks from the Svalis Dome, Barents Sea

Abstract: Eleven shallow cores display 315 m of the >700 m thick Lower and Middle Triasic successional of the Svalis Dome, a Salt diapir in the central south‐western Barents Sea. The Svalis Dome was uplifted in the late Mesozoic. and Trisassic rocks suherop below Quaternary till around the Upper Palaeozoic core of the dome. Deposition of the Triassic succession took place in deep shelf to basinal environments below storm wave base. The succession is dated by macrofossils and palynomorphs and can be assigned to four form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 23 publications
(21 reference statements)
3
46
0
Order By: Relevance
“…11). Shallow cores at the flanks of the Svalis Dome encountered deeper water deposits assigned to the Steinkobbe Formation, representing a setting on a distal outer shelf with restricted circulation (Bugge and Fanavoll, 1995;Mørk and Elvebakk, 1999). Our time-thickness map and paleogeographic reconstruction support a distal development of this sequence in this area.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…11). Shallow cores at the flanks of the Svalis Dome encountered deeper water deposits assigned to the Steinkobbe Formation, representing a setting on a distal outer shelf with restricted circulation (Bugge and Fanavoll, 1995;Mørk and Elvebakk, 1999). Our time-thickness map and paleogeographic reconstruction support a distal development of this sequence in this area.…”
Section: Discussionsupporting
confidence: 62%
“…In the Early to Middle Triassic, the presence of several marine paleo-basins bounded by Late Paleozoic highs may have given rise to local development of anoxic bottom conditions. Moreover, previous authors have suggested general anoxic conditions for the Triassic due to the ancient paleo-Loppa High and generally limited circulation of the basin (Bugge and Fanavoll, 1995;Leith et al, 1993;Mørk and Elvebakk, 1999;. Well 7321/7-1 showed good source rock potential in the Kapp Toscana Group, indicating anoxic water conditions throughout Ladinian to Carnian time in the Barents Sea area (www.npd.no).…”
Section: Reservoir and Source Rock Potentialmentioning
confidence: 93%
See 2 more Smart Citations
“…For paper 1, a total of 144 samples covering the Triassic to the Early Cretaceous age were (Bugge et al, 2002;Mørk and Elvebakk, 1999), mainly from the Svalis Dome and the Nordkapp Basin. In paper 1, such samples are referred to as ''shallow core samples'' and have sample depth between 27 m and 120 m below the seabed (see Table 2 In terms of lithology, most samples studied in paper 1 represent shale or mudstone or claystone.…”
Section: Source Rocks (Papers 1 and 2)mentioning
confidence: 99%